1975
DOI: 10.1212/wnl.25.6.531
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked myotubular myopathy with fatal neonatal asphyxia

Abstract: A second family with X-linked myotubular myopathy is described. The clinical picture includes decreased fetal movements; hydramnios, in at least three cases, probably resulting from insufficient swallowing in utero; and asphyxia at birth. In three autopsy cases many myotubes were found in the muscle tissue. In five definite female carriers, muscle biopsy revealed changes, including myotubes in four. This family probably is not related to the eariler described family with X-linked myotubular myopathy, from whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(22 citation statements)
references
References 0 publications
2
19
1
Order By: Relevance
“…Male patients may al ready be affected at birth [Barth et al, 1975] and others in old age [Harriman and Ilaleem, 1972], It may follow autosomal dominant [Mortier et al, 1975;Karpati et al. 1970], autosomal recessive [Sher et al" 1967] or sexlinked [Barth et al, 1975] modes of inheri tance. Our 4 patients' conditions indicate that the disorder may become apparent at any time of the patient's life.…”
Section: Discussionmentioning
confidence: 99%
“…Male patients may al ready be affected at birth [Barth et al, 1975] and others in old age [Harriman and Ilaleem, 1972], It may follow autosomal dominant [Mortier et al, 1975;Karpati et al. 1970], autosomal recessive [Sher et al" 1967] or sexlinked [Barth et al, 1975] modes of inheri tance. Our 4 patients' conditions indicate that the disorder may become apparent at any time of the patient's life.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 58 cases described in the literature the mode of inheritance has been X-linked in two pedigrees Barth et al, 1975), and autosomal dominant in one family over five generations (McLeod et al, 1972). Sporadic cases are described in 11 further reports although in the original description by Spiro et al (1966), there was distant consanguinity.…”
Section: Geneticsmentioning
confidence: 99%
“…In muscle samples of severe cases of neonatal myotonic dystrophy (Sarnat and Silbert, 1976) certain morphological features similar to those seen in neonatal cases of recessive sex-linked centronuclear myopathy were found by Barth et al (1975). However, in none of the biopsies taken at a later date in neonatal myotonic dystrophy (Karpati et al, 1973;Farkas et al, 1974) was the morphology of centronuclear myopathy found.…”
Section: Discussionmentioning
confidence: 75%